The Effect of Workload and Work-Life Balance on Employee Work Productivity at PT. PG Rajawali II Unit Jatitujuh Majalengka - Erika Uswatun Hasanah; Editya Nurdiana (Interdisciplinary Social Studies, 2026)
In the context of the agro-industrial sector, particularly in sugar manufacturing, employee work productivity is a critical determinant of business performance. PT PG Rajawali II Jatitujuh Unit, as one of the largest sugar industries in Indonesia, faces unique challenges related to high physical labor demands, shift work systems, and intense production target pressures, especially during the sugarcane milling season. These conditions often lead to an increased workload and potential disruption of work-life balance, which can directly affect employee productivity. However, empirical evidence examining the simultaneous influence of workload and work-life balance on productivity in this specific context remains limited. This research is aimed at examining in depth the relationship between workload and work-life balance in influencing employee work productivity at PT PG Rajawali II Jatitujuh Unit. The research uses structured survey-based data collection techniques with an associative quantitative approach to address this issue. The study involved 199 workers, with the Slovin method used to determine the number of respondents completing the survey, resulting in a research sample of 133 people. Data analysis was conducted using SmartPLS software 4. Empirical findings reveal that workload contributes positively and significantly to employee work productivity, as reflected in the original sample value of 0.565 and the significance level with a p-value of 0.000, which is below the threshold of 0.05. Furthermore, work-life balance showed a significant positive influence on employee work productivity, evidenced by the original sample of 0.399 with a p-value of 0.000, which is also below 0.05. Based on these findings, it can be concluded that both independent variables simultaneously increase employee productivity.